2016
DOI: 10.3390/toxins8060175
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Impact of Mild Steaming and Heat Treatment on the Concentration of Okadaic Acid, Dinophysistoxin-2 and Dinophysistoxin-3 in Mussels

Abstract: This study explores the effect of laboratory and industrial steaming on mussels with toxin concentrations above and below the legal limit. We used mild conditions for steaming, 100 °C for 5 min in industrial processing, and up to 20 min in small-scale laboratory steaming. Also, we studied the effect of heat on the toxin concentration of mussels obtained from two different locations and the effect of heat on the levels of dinophysistoxins 3 (DTX3) in both the mussel matrix and in pure form (7-O-palmitoyl okadai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…22 had 30.2 µg/kg of free OA, 183.4 µg/kg of esterified OA, 10.9 µg/kg of free DTX-2, and 22.6 µg/kg of esterified DTX-2, i.e., a total of 247.6 µg/kg. Therefore, the obtained results (Table 2) show that OA, either free or esterified, continue being the main toxin in Galician mollusks and demonstrating that the esterified amount is considerably higher to that in free form, in accordance with previous reports where amount of toxins in the form of the esters is up to 12 times higher [15,18,22]. It is worth mentioning that these three samples contain high levels of the OA group toxins that come from the same common geographical origin (Ría de Arousa) and sell under the same commercial brand for three weeks in a row.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…22 had 30.2 µg/kg of free OA, 183.4 µg/kg of esterified OA, 10.9 µg/kg of free DTX-2, and 22.6 µg/kg of esterified DTX-2, i.e., a total of 247.6 µg/kg. Therefore, the obtained results (Table 2) show that OA, either free or esterified, continue being the main toxin in Galician mollusks and demonstrating that the esterified amount is considerably higher to that in free form, in accordance with previous reports where amount of toxins in the form of the esters is up to 12 times higher [15,18,22]. It is worth mentioning that these three samples contain high levels of the OA group toxins that come from the same common geographical origin (Ría de Arousa) and sell under the same commercial brand for three weeks in a row.…”
Section: Resultssupporting
confidence: 90%
“…Results showed that the regulated toxins OA (RT = 4.18 min), DTX-2 (RT = 4.31 min), PTX-2 (RT = 4.38 min), AZA-2 (RT = 4.9 min), and the emerging toxin SPX-13 (RT = 2.75 min) were found in a number of the analyzed samples. This is the typical toxin profile in the Galician coast, where OA and DTX-2 occur due to Dynophisis acuta and Dynophisis acuminata [22], PTX-2 occur due to D. acuta and Dynophisis caudata [23], and AZA-2 are produced by Azadinium spp. [24].…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, these compounds are known as conjugated and non-active forms. DTX-3 is included in the DST group as they become toxic after the hydrolysis of acyl chain [ 7 , 11 , 12 ]. The role of transforming the active toxin to DTX-3 is supposed to protect bivalves from DSTs activity [ 13 ].…”
Section: Introductionmentioning
confidence: 99%